CHARLIELLA ROSSAE N. GEN., N. SP., FROM THE TETHYAN REALM: REMARKS ON THE EVOLUTION OF LATE PERMIAN BISERIAMMINIDS - Altiner D.; Özkan-Altiner S. (My University, 2001)
The name Charliella is proposed for a new biseriam-minid genus characterized by a four-layered wall that I thickens along the anterior side of the septa and partially occludes the chamber cavity. Charliella rossae was derived from the Globivalvulina graeca-Globivalvulina vonderschmitti lineage which also constituted the root stock of true Paraglobivalvulina (P mira) in Late Permian time. The Globivalvulina decrouezae-Septoglobival-vulina gracilis-Paraglobivalvulinoides septulifer lineage is another trend in the evolution of biseriamminids. The recognition of such a lineage in the Late Permian necessitates taxonomic revision of the biseriamminids to attribute globular and involute forms with thin and undifferentiated walls to Septoglobivalvulina, a genus which was synonymized under Paraglobivalvulina in previous work.
Keywords: Permian; Charliella; Tethyan realm; Paleozoic::Permian; Палеозой::Пермская